Awareness, access and adoption of climate information services for climate change adaptation in Ethiopia - Yohannes Yona; Getachew Sime; Tafesse Matewos (Climate Services, 2025)
Climate change-induced impacts have affected smallholder farmers and their livelihoods in developing countries. The situation in Ethiopia is especially severe due to the prevalence of rain-fed agriculture and the limited availability of climate information services. Smallholder farmers were unable to apply climate adaptation methods due to limited access to and use of climatic information. This study was carried out in Ethiopia’s Sidama region to analyze the current state and factors impacting access to and use of climate information services as decision-making tools for climate change adaptation. Employing a mixed research strategy, data was collected from 403 sample households, 32 key informants, and 6 focus group discussions to address the study objectives. The collected data was analyzed using both descriptive and inferential statistics. Specifically, the Heckman probit econometric model was employed to identify the factors that affect the access to and utilization of climate information services in the study districts. The study discovered that smallholder farmers obtain climate information through various sources, such as personal experience, community meetings, extension services, and mass-media. Despite 65.8 percent of surveyed households recognizing the importance of climate information for decision-making, only 44.4 percent of the respondents implemented it in their agricultural activities. This disparity can be attributed to various socioeconomic, institutional, and farmers’ characteristics. The study emphasized the need for capacity-building training, improved access to infrastructure like Farmer Training Centers (FTCs), and the integration of climate information with extension services to enhance the implementation of strategies to adapt to climate change in the region.